2020
DOI: 10.37213/cjal.2020.28736
|View full text |Cite
|
Sign up to set email alerts
|

Agentive Apprenticeship of Observation and English Teacher Identity: A Pakistani Case of Learning to Teach English

Abstract: An exploration of literature on second/foreign language (L2/FL) teaching suggests that the phenomenon in question has been investigated either by examining classroom processes or by exploring teachers’ lived experiences. Situated in the latter area, this paper reports a qualitative study that understands how Pakistani primary school teachers learn to teach English—the subject mandated in recent curricular reforms—and develop their English teacher identity. The findings problematize the apprenticeship of observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…As a result, the teacher would guide the students in the same way they were educated. This is also in line with the finding by Lortie (1975) in (Chana, 2020), she stated in teacher education this is called as the apprenticeship of observation, which means when the teachers entered the profession, they use the learning model as how they were taught in the teaching process, thus give a conservative pressure on the profession.…”
Section: Discussionsupporting
confidence: 83%
“…As a result, the teacher would guide the students in the same way they were educated. This is also in line with the finding by Lortie (1975) in (Chana, 2020), she stated in teacher education this is called as the apprenticeship of observation, which means when the teachers entered the profession, they use the learning model as how they were taught in the teaching process, thus give a conservative pressure on the profession.…”
Section: Discussionsupporting
confidence: 83%
“…Teachers' language learning experiences do play a role in shaping their character as a teacher (Borg, 2004; Channa, 2020), but not as a list of what to do and what to avoid in terms of teaching technicalities (Gray, 2020; Moodie, 2016). Some previous studies have shown that conceptions of teaching that are gained as a language learner may be “agentively and innovatively utilized” (Channa, 2020, p. 132) and “reshaped a great deal” (Huang et al., 2021, p. 193). This can be particularly significant with regard to the formation of teacher's views of their critical sociocultural role and responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…The way Raha, Neda, and Mojdeh steadily carried their language learning experiences over to later stages of their journey particularly offers insights about apprenticeship of observation in relation with constructing teacher's sociocultural sensitivity. Teachers' language learning experiences do play a role in shaping their character as a teacher (Borg, 2004; Channa, 2020), but not as a list of what to do and what to avoid in terms of teaching technicalities (Gray, 2020; Moodie, 2016). Some previous studies have shown that conceptions of teaching that are gained as a language learner may be “agentively and innovatively utilized” (Channa, 2020, p. 132) and “reshaped a great deal” (Huang et al., 2021, p. 193).…”
Section: Discussionmentioning
confidence: 99%
“…The word "identity" has become widely used by English communities in language learning and teaching since the beginning of the 21 st century. Channan (2020) uses qualitative research method to explore how English teachers in a primary school in Pakistan teach English under the new curriculum reform and how their teacher identity is developed. The study shows teachers prefer to use the way that they like to teach English so as to build their own identity.…”
Section: English Teachers' Professional Identitymentioning
confidence: 99%